The librarian spy : [large type] a novel of World War II - Martin, Madeline (Thorndike Press large print historical fiction., 2022)
"Ava thought her job as a librarian at the Library of Congress would mean a quiet, routine existence. But an unexpected offer from the US military has brought her to Lisbon with a new mission: posing as a librarian while working undercover as a spy gathering intelligence. Meanwhile, in occupied France, Elaine has begun an apprenticeship at a printing press run by members of the Resistance. It's a job usually reserved for men, but in the war, those rules have been forgotten. Yet she knows that the Nazis are searching for the press and its printer in order to silence them. As the battle in Europe rages, Ava and Elaine find themselves connecting through coded messages and discovering hope in the face of war"--